2014
DOI: 10.1056/nejmoa1311593
|View full text |Cite
|
Sign up to set email alerts
|

Radical Prostatectomy or Watchful Waiting in Early Prostate Cancer

Abstract: BACKGROUND Radical prostatectomy reduces mortality among men with localized prostate cancer; however, important questions regarding long-term benefit remain. METHODS Between 1989 and 1999, we randomly assigned 695 men with early prostate cancer to watchful waiting or radical prostatectomy and followed them through the end of 2012. The primary end points in the Scandinavian Prostate Cancer Group Study Number 4 (SPCG-4) were death from any cause, death from prostate cancer, and the risk of metastases. Secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
593
1
38

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 864 publications
(642 citation statements)
references
References 16 publications
10
593
1
38
Order By: Relevance
“…The Scandinavian Prostate Cancer Group Study Number 4 (SPCG-4) randomized 695 patients to radical prostatectomy versus watchful waiting with a median follow up time of 13.4 years [6]. The mean age was 65 years, the mean PSA value was 13 ng/mL and the majority of the participants had locally advanced disease, diagnosed on digital rectal examination and therefore palpable.…”
Section: Active Surveillance and Watchful Waitingmentioning
confidence: 99%
See 2 more Smart Citations
“…The Scandinavian Prostate Cancer Group Study Number 4 (SPCG-4) randomized 695 patients to radical prostatectomy versus watchful waiting with a median follow up time of 13.4 years [6]. The mean age was 65 years, the mean PSA value was 13 ng/mL and the majority of the participants had locally advanced disease, diagnosed on digital rectal examination and therefore palpable.…”
Section: Active Surveillance and Watchful Waitingmentioning
confidence: 99%
“…A reduction of 12.7 percentage points for cumulative incidence of death from any cause and 17.7 percentage points for prostate cancer-related cumulative incidence of death confirmed a substantial reduction in mortality after radical prostatectomy. In addition, it was concluded that prostatectomy reduced the risk of metastatic disease and the need for androgen deprivation therapy [6].…”
Section: Active Surveillance and Watchful Waitingmentioning
confidence: 99%
See 1 more Smart Citation
“…In that trial, 695 men were randomised to radical prostatectomy (n = 347) or watchful waiting (n = 348) with a median follow-up of 12 years. Overall, there was a significant disease-specific survival advantage for men treated with surgery, but a more recent analysis has indicated that this benefit was greatest for men either 65 years old or younger or with intermediate disease risk at diagnosis [18]. In the PIVOT trial, radical prostatectomy (n = 367) was compared with watchful waiting (n = 364) with a primary outcome of all-cause mortality and secondary outcomes of prostate specific mortality, metastases and symptoms in a largely screen-detected population.…”
Section: Evidence Versus Belief; Does Definitive Local Therapy Cure Pmentioning
confidence: 99%
“…Radical prostatectomy remains standard of care for organ-confined prostate cancer and provides excellent oncological outcomes (1,2). During radical prostatectomy, the continuity of the lower urinary tract is disrupted to allow for complete en-bloc prostate resection and is later restored by means of vesicourethral anastomosis (VUA).…”
Section: Introductionmentioning
confidence: 99%